Effects of gasification temperature and equivalence ratio on gasification performance and tar generation of air fluidized bed gasification using raw and torrefied empty fruit bunch - Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (AIDIC Servizi, 2021)
This paper presents gasification performance study and tar generation at different gasification temperature and equivalence ratio using air fluidized bed gasification process. Empty fruit bunch (EFB) is selected as feedstock where two types of EFB were used which are raw EFB and EFB undergo torrefaction process as pretreatment. Experimental results show the synthesis gas yield, lower heating value (LHV), cold gas efficiency (CGE) and tar generation are steadily increased for both feedstock when gasification temperature is increased from 700 to 900°C. When ER is increased from 0.26 to 0.33 at fixed gasification temperature of 900°C, all gasification performances except LHV show an increment trend. Torrefied EFB shows superior performance in terms of producing more synthesis gas and better LHV compared to raw EFB. However, tar generated from torrefied EFB is higher than raw EFB. Based on tar component analysis, it has been found that 7 tar components are detected where all of tar components are classified as tertiary polycyclic aromatic hydrocarbons (PAHs) group for both feedstocks. Based on tar analysis, naphthalene is the most produced tar components obtained from gasification of raw and torrefied EFB.